The Role Of Consumer Trust In Ai-Driven Personalized Marketing And Purchase Decisions - Mufidatul Azmi; Chairunnisaa Miftahurrahmah Zenida Huzaen; Ade Vidya Eryanti (Sekolah Tinggi Ilmu Ekonomi Amkop Makassar, 2026)
This study examines the role of AI-Driven Consumer Trust in mediating the relationship between AI-Driven Personalized Marketing and Consumer Decision-Making among Generation Z consumers in Makassar, Indonesia. A quantitative explanatory design was employed, and data were collected from 128 respondents using purposive sampling. The data were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM). The findings indicate that AI-driven personalized marketing significantly influences consumer decision-making both directly and indirectly through consumer trust, confirming a partial mediating effect. These results suggest that while personalization enhances the relevance and effectiveness of marketing content, its impact on decision-making is strengthened when consumers develop trust in AI-based systems. Conversely, ethical and privacy implications were not found to have a significant direct effect on consumer decision-making. This finding implies that, within the Generation Z context, perceived practical benefits such as relevance and convenience tend to outweigh normative concerns related to data ethics and privacy. The study contributes to the literature by providing empirical evidence on the mediating role of trust in AI-driven marketing within an emerging market context.